Concentration and competition among NBFC-MFI'S in India - S, Vignesh; G. Menon, Dileep; Vivek Menon, Remya (International Journal of Engineering and Technology, 2018)
Non-banking financial companies have a prominent role in the development of Indian economy. A stable non-banking system is essential for growth and development of any economy. In India, the NBFC's started proliferating during the year 1956. Primary aspects that influence the Non-Banking Industry’s progress are the competition that arises between them. This research aims at investigating the competition level of NBFC-MFI's (Micro Financial Institutions) in India by using an assessment methodology which focuses on analyzing the overall com-petitiveness of the NBFC-MFI's in India in accordance to the standards of market concentration ratio. Here the competition level of NBFC-MFI's in India is analyzed using Herfindahl-Hirschman Index. We also estimate the Concentration Ratio for the industry. The analysis is done for the NBFC-MFI's registered with RBI as on 2018 for the period from 2000-2017. The research results highlighted that the Non-Banking Financial Companies in India was characterized, during the year 2017, by an oligopoly competition with the dominant company with competitive edges or monopoly.